The assessment of didactic: cooperative approach in teenagers during physical education contexts - Castelnuovo, Cecilia; Zottola, Amedeo; Lovecchio, Nicola (Formazione & insegnamento, 2019)
Actually the mission of the school turn in favour of a new expertise (the life skills) adopting the cooperative learning approach: team work, briefing and collaboration to improve the ability to solve problem. The cooperative learning was applied during Physical Education classes in high school context. The goodness of the approach was assessed by pre-post administration of two questionnaire: PACES and SELF-EFFICACY for enjoyment and efficacy perceived, respectively. The data analysis showed that cooperative teaching methods improved the sense of individual and collective self-efficacy keeping the level of enjoyment.